Sistem Informasi Kursus IBAY Komputer Berbasis Web dan Mobile Android - Iwan Purnama (RJOCS (Riau Journal of Computer Science), 2019)
Ibay Computer Course and Training Institution (LKP) is a Computer Education Center the best choice of computer courses for Rantauprapat and outside the city of Rantauprapat because the courses are up to and accredited B. Currently Ibay Computers serve computer courses starting from Office Operators, Programming, Computer Technicians , Computer Networks, Multimedia, Internet, Autoca, Animation and Other Computer Courses. But now all recording transactions at Ibay Computers still use a manual system, so that all recording processes are less accurate. In addition, the course payment process is still recorded manually and inaccurately, because it must count one by one transactions that occur every day. Therefore an information technology-based system is needed to correct old system weaknesses. In making this new information system, it is intended to be able to record income and expenditure transactions quickly and accurately. And can display monthly reports quickly and accurately to the owner of a computer course. In addition, this new information system provides online registration facilities where prospective participants can register themselves through the website or Android application. The old system analysis process by conducting a survey to the computer course Ibay Computer. From the results of testing the new information system, it can record income and expenses accurately, and course participants can register their own course schedules through the website. And can display all reports to the owner. And from the results of a questionnaire filled by 5 correspondents, it was found that the overall application evaluation results were 87% good